IoT, building Arduino-based projects : explore and learn about Internet of Things to develop interactive Arduino-based internet projects.: explore and learn about Internet of Things to develop interactive Arduino-based internet projects. (2016) - Waher, Peter; Seneviratne, Pradeeka; Russell, Brian; Van Duren, Drew
No abstract available